Intensity modulated or fractionated stereotactic reirradiation in patients with recurrent nasopharyngeal cancer - Röder, Falk; Zwicker, Felix; Saleh-Ebrahimi, Ladan; Timke, Carmen; Thieke, Christian; Bischof, Marc; Debus, Jürgen; Huber, Peter E. (Radiation oncology, 2011)
Purpose: To report our experience with intensity-modulated or stereotactic reirradiation in patients suffering from recurrent nasopharyngeal carcinoma. Patients and Methods: The records of 17 patients with recurrent nasopharygeal carcinoma treated by intensity-modulated (n = 14) or stereotactic (n = 3) reirradiation in our institution were reviewed. Median age was 53 years and most patients (n = 14) were male. The majority of tumors showed undifferentiated histology (n = 14) and infiltration of intracranial structures (n = 12). Simultaneous systemic therapy was applied in 8 patients. Initial treatment covered the gross tumor volume with a median dose of 66 Gy (50-72 Gy) and the cervical nodal regions with a median dose of 56 Gy (50-60 Gy). Reirradiation was confined to the local relapse region with a median dose of 50.4 Gy (36-64Gy), resulting in a median cumulative dose of 112 Gy (91-134 Gy). The median time interval between initial and subsequent treatment was 52 months (6-132). Results: The median follow up for the entire cohort was 20 months and 31 months for survivors (10-84). Five patients (29%) developed isolated local recurrences and three patients (18%) suffered from isolated nodal recurrences. The actuarial 1- and 2-year rates of local/locoregional control were 76%/59% and 69%/52%, respectively. Six patients developed distant metastasis during the follow up period. The median actuarial overall survival for the entire cohort was 23 months, transferring into 1-, 2-, and 3-year overall survival rates of 82%, 44% and 37%. Univariate subset analyses showed significantly increased overall survival and local control for patients with less advanced rT stage, retreatment doses > 50 Gy, concurrent systemic treatment and complete response. Severe late toxicity (Grad III) attributable to reirradiation occurred in five patients (29%), particularly as hearing loss, alterations of taste/smell, cranial neuropathy, trismus and xerostomia. Conclusion: Reirradiation with intensity-modulated or stereotactic techniques in recurrent nasopharyngeal carcinoma is feasible and yields encouraging results in terms of local control and overall survival in patients with acceptable toxicity in patients with less advanced recurrences. However, the achievable outcome is limited in patients with involvement of intracranial structures, emphasising the need for close monitoring after primary therapy.
Gesehen am 19.09.2022